Early Signs of Pathological Cognitive Aging in Mice Lacking High-Affinity Nicotinic Receptors - Konsolaki, Eleni; Tsakanikas, Panagiotis; Polissidis, Alexia V.; Stamatakis, Antonios; Skaliora, Irini (Frontiers in Aging Neuroscience, 2016)
In order to address pathological cognitive decline effectively, it is critical to adopt early preventive measures in individuals considered at risk. It is therefore essential to develop approaches that identify such individuals before the onset of irreversible dementia. Α deficient cholinergic system has been consistently implicated as one of the main factors associated with a heightened vulnerability to the aging process. In the present study we used mice lacking high affinity nicotinic receptors (β2-/-), which have been proposed as an animal model of accelerated/premature cognitive aging. Our aim was to identify behavioural signs that could serve as indicators or predictors of impending cognitive decline. We used test batteries in order to assess cognitive functions and additional tasks to investigate spontaneous behaviours, such as species-specific activities and exploration/locomotion in a novel environment. Our data confirm and extend the hypothesis that β2-/- animals exhibit age-related cognitive impairments, manifested in both spatial learning and recognition memory tasks. In addition, we reveal deficits in spontaneous behaviour and habituation processes earlier in life. To our knowledge, this is the first study to perform an extensive behavioural examination of an animal model of premature cognitive aging, and our results suggest that β2-nAChR dependent cognitive deterioration progressively evolves from initial subtle behavioural changes to global dementia due to the combined effect of the neuropathology and aging.